2009
DOI: 10.1002/bmc.1230
|View full text |Cite
|
Sign up to set email alerts
|

Simple and rapid micro‐scale quantification of artemisinin in living Artemisia annua L. by improved gas chromatography with electron‐capture detection

Abstract: Malaria threatens 300-500 million people and kills more than one million people annually. Artemisinin has been widely used as part of the artemisinin-based combination therapies against malaria. However, its supply is seriously short due to very small amounts of production of artemisinin in Artemisia annua. Molecular biologic researches aimed at increasing the artemisinin yield in plant have received more and more attention and therefore corresponding quantification methods for artemisinin analysis are urgentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 33 publications
2
3
0
Order By: Relevance
“…The artemisinin in A . annua is partly degraded into three major compounds under the high temperature produced by GC, and four peaks pertaining to artemisinin appeared on the chromatogram, in agreement with previous reports (Liu et al ). The second most abundant compound in wild‐type was camphor (0.72 mg g −1 dry weight (DW)), whereas borneol, a reduced form of camphor, was the second most prevalent compound in the iar mutant.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The artemisinin in A . annua is partly degraded into three major compounds under the high temperature produced by GC, and four peaks pertaining to artemisinin appeared on the chromatogram, in agreement with previous reports (Liu et al ). The second most abundant compound in wild‐type was camphor (0.72 mg g −1 dry weight (DW)), whereas borneol, a reduced form of camphor, was the second most prevalent compound in the iar mutant.…”
Section: Resultssupporting
confidence: 92%
“…Gas chromatography‐mass spectrometry (GC‐MS) analysis of terpenoids of A . annua leaves was performed according to the method previously reported (Liu et al ) using an Agilent 7890N GC system (Santa Clara, CA) with a flame ionization detector and an electron ionization source.…”
Section: Methodsmentioning
confidence: 99%
“…For compound 1 , four peaks were formed (as shown in Fig. ) owing to the thermal degradation of artemisinin, which was consistent with previous reports (Peng et al , ; Liu et al , ). The results showed that the purity of compounds 1–3 was 99.1, 99.6 and 99.3% respectively.…”
Section: Resultssupporting
confidence: 91%
“…GC analysis of artemisinin was performed according to the previously reported method (Liu et al , ) using an Agilent 6890N GC system (Santa Clara, CA, USA) with a flame ionization detector. Briefly, 1.0 μL of sample was injected to a HP‐5 capillary column (Agilent).…”
Section: Methodsmentioning
confidence: 99%
“…Current analytical techniques describe derivatisation-based methods [22] , gas chromatography (GC) [23] , thin layer chromatography (TLC) [24] , supercritical fluid chromatography (SCFC) [25] , spectroscopic [26] and immunological techniques [27] , [28] , but it is clear that the main-stream methods are mainly based on high performance liquid chromatography (HPLC), coupled to ultra violet (UV), evaporative light scattering detector (ELSD), electron capture detection (ECD) or electrospray ionisation (ESI)–mass spectrometry (MS) detection [29] , [30] , [31] , [32] . Up till now, the focus was directed to biological matrices like plasma for pharmacokinetic information [33] , [34] , to plant derived samples for production reasons [23] , [35] , [36] or for environmental eco-toxicity studies [37] , [38] . However, with the advent of a plethora of newly developed 1,2,4-trioxane derivatives and the urgent demand to develop suitable paediatric formulations, there is a clear need for analytical methods which are suitable for quality purposes for finished drug products (FDP).…”
Section: Introductionmentioning
confidence: 99%